Detection of Low Radar Cross Section (RCS) Targets in Sea Clutter Environments using Pulse-Doppler Radar Simulation - Muhammad Rendra Perdana Kusuma Djaka; Edo Lutfi Mahanani; Muhammad Dhafin Sulaiman Al Rasyid; Uke Kurniawan Usman (Institut Teknologi Dirgantara Adisutjipto, 2026)
This paper reports a simulation-based investigation of low-radar-cross-section (low-RCS) maritime target detection using a pulse–Doppler radar operating in K-distributed sea clutter environments. The results indicate that heavy-tailed clutter statistics significantly deteriorate the performance of conventional cell-averaging CFAR (CA-CFAR), particularly under low signal-to-clutter ratio (SCR) and nonhomogeneous clutter conditions. Range–Doppler analysis confirms that coherent Doppler integration and MTI filtering increase target-to-clutter contrast; however, substantial residual clutter persists in rough sea states. A comparative evaluation demonstrates that ordered-statistics CFAR (OS-CFAR) consistently provides superior performance, achieving higher detection probability, enhanced robustness to clutter transitions, stable false alarm regulation, and improved threshold stability. At a detection probability of 0.8, OS-CFAR attains an SCR advantage of approximately 2–3 dB over CA-CFAR under severe clutter conditions. The results further reveal the influence of Doppler ambiguity and blind speed effects, highlighting the necessity of jointly considering detection algorithms and waveform design to achieve reliable maritime radar operation.